2022
DOI: 10.1186/s12936-022-04046-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in the incidence of malaria diagnosed at public health facilities in Uganda

Abstract: Background Routine malaria surveillance data in Africa primarily come from public health facilities reporting to national health management information systems. Although information on gender is routinely collected from patients presenting to these health facilities, stratification of malaria surveillance data by gender is rarely done. This study evaluated gender difference among patients diagnosed with parasitological confirmed malaria at public health facilities in Uganda. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 38 publications
4
17
0
Order By: Relevance
“…Parasitaemia rates were significantly (p < 0.001) and consistently higher in male donors (13.1%) compared with female donors (7.4%), irrespective of location or month of collection. This male bias of parasitologically confirmed malaria infection prevalence is in keeping with several other studies conducted in Africa [ 24 , 27 , 29 , 30 ]. Interestingly, different temporal trends for male and female donor malaria prevalence were observed, with males mirroring the generally reported seasonal increase from November to April and female donors having a more stable malaria prevalence over time (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Parasitaemia rates were significantly (p < 0.001) and consistently higher in male donors (13.1%) compared with female donors (7.4%), irrespective of location or month of collection. This male bias of parasitologically confirmed malaria infection prevalence is in keeping with several other studies conducted in Africa [ 24 , 27 , 29 , 30 ]. Interestingly, different temporal trends for male and female donor malaria prevalence were observed, with males mirroring the generally reported seasonal increase from November to April and female donors having a more stable malaria prevalence over time (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…This disproportionate burden has been widely reported both in Uganda and globally [ 4 , 8 , 16 , 20 ]. In addition, females were twice as affected as males., a finding reported previously in multiple districts of Uganda [ 21 ]. Females in Kole District might engage in activities that increase their exposure to mosquitoes.…”
Section: Discussionsupporting
confidence: 81%
“…During our study, we observed that cooking areas were outside the house, meaning that women would likely be exposed in the evenings while preparing meals. It should be noted that in comparison to males, females are also more likely to report fevers to health facilities and have more opportunities to be tested for malaria during child health care or antenatal visits [ 21 ]. However, pregnancy may also increase susceptibility [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In areas with high prevalence, the most vulnerable groups are young children, who have not yet developed immunity to malaria, and pregnant women, whose immunity has been decreased due to pregnancy [ 3 ]. In low-prevalence areas, the women generally have developed no immunity to malaria [ 4 ]. Malaria infection is the major cause of maternal anemia, premature delivery, and fetal loss [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In low-prevalence areas, the women generally have developed no immunity to malaria [ 4 ]. Malaria infection is the major cause of maternal anemia, premature delivery, and fetal loss [ 3 , 4 ]. For equal exposure, adult men and women are equally vulnerable to malaria infection, but pregnant women are at greater risk of malaria infection [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%